Teratoid wilms tumor: Case Report and Review of Literature - Agarwal, Kiran; Anand, Amrita; Singh, Smita; Suman, Neha (Journal of Pediatric Nephrology, 2020)
Teratoid Wilm’s tumor is a rare variant of Wilm’s tumor, which composed of well-differentiated epithelial cells or mesenchymal heterologous elements constituting more than 50% of the conventional wilm’s tumors in pediatric group. We hereby report an additional case in a 6-year-old female along with review of literature.